Admission Orientation Menurunkan Stres Pasien Awal Masuk Rumah Sakit - Kusnanto Kusnanto; Siti Guntarlin; Dian Nur Arisandi (Universitas Airlangga, 2007)
Introduction: Being hospitalized, some people may encounter a strange environment and situation which trigger stress to the patients. By giving an orientation, patients will learn how to adapt to this stressful event. Admission Orientation is a type of orientation which can be given to the patient on early stage of hospitalization. The main purpose of Admission Orientation is to facilitate the patients to cope with hospital environment and situation at first 24-48 hours. The objective of this study was to analyze the effect of admission orientation to reduce the stress level in early hospitalized patients. Method: A quasy experimental design was used in this study. Population had taken from new patient in C (Cempaka) Surgical Ward, on June 2007. Sample were recruited by using total sampling and there were 12 samples who met to the inclusion criterias, divided into 6 samples for intervention group and 6 samples for control group. The independent variable was Admission Orientation and the dependent variable was stress responses. Data were collected by using questionnaire and analyzed by using Wilcoxon Signed Ranks Test and Mann-Whitney U Test with significance level α≤0.05. Result: The result showed that Admission Orientation reduce the stress level in early hospitalized patients with p=0.025 in intervention group, p=0.157 in control group.Discussion: It can be concluded that Admission Orientation reduce patient’s level of stress. Therefore, Admission Orientation should be applied on hospitals as a program that can promote patient’s adaptation in early hospitalization.